Effect on the Skin Microbiota of Oral Minocycline for Rosacea - Yiyi Zhang; Ying Zhou; Philippe Humbert; Dengfeng Yuan; Chao Yuan (Medical Journals Sweden, 2023)
In the rosacea an unstable skin microbiota is significant for disease progression. However, data on the influence on the skin microbiota of treatment with systemic antibiotics are limited. This single-arm trial recruited patients with rosacea. Oral minocycline 50 mg was administered twice daily for 6 weeks. The lesions on the cheek and nose were sampled for 16S rRNA amplicon sequencing and metagenomic sequencing at baseline, 3 weeks and 6 weeks of treatment. Physiological parameters were detected using non-invasive instruments. After treatment, distribution of the Investigator Global Assessment scores changed significantly. For the skin microbiota, a notable increase in α-diversity and a shift of structure were observed after treatment. Treatment was accompanied by a reduction in the relative abundance of Cutibacterium and Staphylococcus, indicating negative correlations with increased bacterial metabolic pathways, such as butyrate synthesis and L-tryptophan degradation. The increased butyrate and tryptophan metabolites would be conducive to inhibiting skin inflammation and promoting skin barrier repair. In addition, the abundance of skin bacterial genes related to tetracycline resistance and multidrug resistance increased notably after antibiotic treatment.